2015
DOI: 10.1021/mp500872g
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evaluation of Molecular States of Piroxicam/Poloxamer Nanosuspension by Suspended-State NMR and Raman Spectroscopies

Abstract: A nanosuspension of piroxicam (PXC) and poloxamer 407 (poloxamer) prepared by the wet milling method was directly evaluated at the molecular level from the viewpoint of both solution and solid phases. (13)C solution-state NMR measurements revealed a reduction in the concentration of dissolved poloxamer in the nanosuspension. Furthermore, the fraction of dissolved poly(ethylene oxide) (PEO) chain, which is the hydrophilic part of poloxamer, was higher than that of dissolved poly(propylene oxide) (PPO) chain, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…In the topdown method, the drug first forms a suspended state. It has been inferred that this nanosuspension consists of crystalline API core particles surrounded by a semi-solid phase of a drug and a stabilizer (25,26). The semi-solid phase on the surface of the nanoparticles is in equilibrium with the solution and promotes stabilization of the nanoparticles by steric hindrance and electrostatic repulsion (25,26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the topdown method, the drug first forms a suspended state. It has been inferred that this nanosuspension consists of crystalline API core particles surrounded by a semi-solid phase of a drug and a stabilizer (25,26). The semi-solid phase on the surface of the nanoparticles is in equilibrium with the solution and promotes stabilization of the nanoparticles by steric hindrance and electrostatic repulsion (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…It has been inferred that this nanosuspension consists of crystalline API core particles surrounded by a semi-solid phase of a drug and a stabilizer (25,26). The semi-solid phase on the surface of the nanoparticles is in equilibrium with the solution and promotes stabilization of the nanoparticles by steric hindrance and electrostatic repulsion (25,26). In addition to the top-down approaches described above, there is also a bottom-up approach, whereby prepared ASDs are placed under controlled temperature and humidity to form a CSD (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional solution-state NMR and solid-state NMR techniques have been widely used in various fields. , In addition, suspended-state NMR or in situ NMR, a technique in which solid-state NMR is applied to samples containing a mixture of solid and dissolved components, is also often used to investigate a whole suspension sample without preprocessing and has clarified some of the unique features of nanosuspensions. In a study of nanoparticles in pharmaceutical applications, Zhang et al observed solid–liquid exchange between probucol and the polyvinylpyrrolidone/sodium dodecyl sulfate complex at the surface of the nanoparticle by 13 C solution-state NMR measurement . Hasegawa et al investigated piroxicam/poloxamer nanoparticles using suspended-state NMR and reported that piroxicam nanocrystals formed a core–shell structure with crystalline and amorphous piroxicam surrounded by poloxamer chains . Although these studies successfully determined the interfacial structure of the nanoparticles, directly observing the surface structure of the nanoparticles was difficult.…”
Section: Introductionmentioning
confidence: 99%
“…23 Hasegawa et al investigated piroxicam/poloxamer nanoparticles using suspended-state NMR and reported that piroxicam nanocrystals formed a core−shell structure with crystalline and amorphous piroxicam surrounded by poloxamer chains. 24 Although these studies successfully determined the interfacial structure of the nanoparticles, directly observing the surface structure of the nanoparticles was difficult. The surface structures of the amorphous drug and polymeric stabilizing agents were thought to be in the intermediate mobility region between solid and solution; hence, neither solid-nor solution-state NMR was able to detect the signals from the surface structure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…All the suspensions separate on standing. For the formulator, it is one of the main concerns is to permit easy resuspendibilty of settled particulate matter but also to decrease the sedimentation rate [3].…”
Section: Introductionmentioning
confidence: 99%